ASAS LEGALITAS DALAM HUKUM PIDANA SEBAGAI INSTRUMEN PERLINDUNGAN HAK ASASI MANUSIA - S, Laurensius Arliman; Hutajulu, Maria Margaeta (Ensiklopedia of Journal, 2026)
Abstract: The principle of legality is one of the fundamental principles in criminal law that functions as a limitation on state power as well as an instrument for the protection of human rights. This principle affirms that no act may be punished without a prior provision of criminal law that was in force at the time the act was committed. The existence of the principle of legality is crucial in ensuring legal certainty, preventing arbitrary actions by law enforcement authorities, and protecting individual rights from retroactive criminalization. This study aims to analyze the position, meaning, as well as the concept and function of the principle of legality within the Indonesian criminal law system as a guarantee of human rights protection, particularly following the enactment of Law Number 1 of 2023 concerning the Criminal Code. The research employs a normative legal research method with a historical legal approach, examining the development of the principle of legality from classical criminal law to its reformulation in the national Criminal Code. The findings indicate that the principle of legality is no longer understood merely in a formal sense through the principles of lex scripta, lex certa, and lex praevia, but has also undergone an expansion of meaning through the recognition of living law in society, insofar as it is consistent with the values of Pancasila, the 1945 Constitution of the Republic of Indonesia, and human rights. The reformulation of the principle of legality in Law Number 1 of 2023 reflects an effort to balance legal certainty and substantive justice without diminishing its primary function as a protector of human rights. Accordingly, the principle of legality continues to occupy a central position in the Indonesian criminal law system as a foundation of a state governed by law that upholds the protection of human rights.Keywords: Principle of Legality, Criminal Law, Human Rights.